2021
DOI: 10.1038/s41467-021-23372-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular motion and tridimensional nanoscale localization of kindlin control integrin activation in focal adhesions

Abstract: Focal adhesions (FAs) initiate chemical and mechanical signals involved in cell polarity, migration, proliferation and differentiation. Super-resolution microscopy revealed that FAs are organized at the nanoscale into functional layers from the lower plasma membrane to the upper actin cytoskeleton. Yet, how FAs proteins are guided into specific nano-layers to promote interaction with given targets is unknown. Using single protein tracking, super-resolution microscopy and functional assays, we link the molecula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 74 publications
5
24
0
Order By: Relevance
“…This strongly suggested that the layered nature is the result of a cell-type-independent organising principle that persists throughout FA maturation stages. A plethora of subsequent studies employing a range of different techniques, culturing methods and cell types further investigated this layered nanostructure [40][41][42][43][44][45]. The cell-type-independent nature was shown by the diversity of cell types studied, which are from different species (human, mouse and simian) and include both carcinogenic and non-carcinogenic cells.…”
Section: The Molecular Composition Of Focal Adhesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This strongly suggested that the layered nature is the result of a cell-type-independent organising principle that persists throughout FA maturation stages. A plethora of subsequent studies employing a range of different techniques, culturing methods and cell types further investigated this layered nanostructure [40][41][42][43][44][45]. The cell-type-independent nature was shown by the diversity of cell types studied, which are from different species (human, mouse and simian) and include both carcinogenic and non-carcinogenic cells.…”
Section: The Molecular Composition Of Focal Adhesionsmentioning
confidence: 99%
“…Two very recent studies point towards the biological importance of preserving the layered nanostructure of FAs [44,45]. The first study revealed that the chlamydial protein Translocated actin-recruiting Phosphoprotein (TarP) is targeted to FAs by vinculin, where it increased FA stability and inhibited cell motility [44].…”
Section: Fa Proteins Are Not Strictly Separated Into Layersmentioning
confidence: 99%
“…Segments with a minimum length of 20 frames (400 ms) were classified into diffusion states as previously reported (Rossier et al, 2012;Harwardt et al, 2017;Orré et al, 2021). First, the segments were separated into immobile and mobile diffusion applying a diffusion coefficient threshold D min .…”
Section: Msd(δt) 4dδtmentioning
confidence: 99%
“…For this analysis, single trajectories were divided into segments showing uniform movement. These segments were analyzed separately with regard to their diffusion mode (free, confined, immobile) (Rossier et al, 2012;Harwardt et al, 2017;Orré et al, 2021). In addition, we extracted the transitions between different segments within single trajectories, which report on functional transitions of the MET receptor signaling complex.…”
Section: Introductionmentioning
confidence: 99%
“…A few years ago, interferometric photoactivated localization microscopy (iPALM) has revealed a layered organization of integrin-containing FAs ( Kanchanawong et al, 2010 ; Case et al, 2015 ). This model, proposing the spatial segregation of specific adhesome components between a integrin signaling layer (closest to the membrane), a force transduction layer, and an actin regulatory layer (innermost), has been endorsed by studies making advantage of diverse techniques, such as single protein tracking microscopy, superresolution microscopy, proximity biotinylation, and bimolecular fluorescence complementation ( Dong et al, 2016 ; Chastney et al, 2020 ; Legerstee and Houtsmuller, 2021 ; Orre et al, 2021 ; Ripamonti et al, 2021 ). Despite these great advances, the characterization of several structural and mechanical aspects of the sophisticated integrin-dependent protein network, a comprehensive understanding of the FA machinery is still far from being accomplished ( Chastney et al, 2020 ; Legerstee and Houtsmuller, 2021 ).…”
Section: Introductionmentioning
confidence: 99%